2013
DOI: 10.1080/09603123.2012.699031
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndromes related to bio-climate in a Mediterranean area. The case of Ierapetra, Crete Island, Greece

Abstract: The occurrence of non-fatal acute coronary syndromes (ACS) is examined in relation with the local bioclimatic conditions in the Ierapetra area, in the southernmost part of Crete Island, Greece, during the period 2004-2007. Daily ACS counts and corresponding meteorological parameters, such as maximum and minimum air temperature, relative humidity, wind speed and cloudiness, were analyzed. Besides, the daily values of the human thermal index, physiologically equivalent temperature (PET) was evaluated. Pearson's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
2
19
0
4
Order By: Relevance
“…This study indicated that the extremely hot temperatures increased the risk of ACS hospitalisation, but the cold temperature did not show any effect on ACS admission. This result is consistent with other investigations indicating hot weather is responsible for the most part of the temperature-related ACS admission 24. In contrast, a study reported the occurrence of acute myocardial infarction was associated with low temperatures,25 and the study conducted by Wolf et al 3 showed that the risk for the occurrence of myocardial infarction was similar in winters and summers, which was non-significant.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study indicated that the extremely hot temperatures increased the risk of ACS hospitalisation, but the cold temperature did not show any effect on ACS admission. This result is consistent with other investigations indicating hot weather is responsible for the most part of the temperature-related ACS admission 24. In contrast, a study reported the occurrence of acute myocardial infarction was associated with low temperatures,25 and the study conducted by Wolf et al 3 showed that the risk for the occurrence of myocardial infarction was similar in winters and summers, which was non-significant.…”
Section: Discussionsupporting
confidence: 88%
“…Our study showed seasonal variations in ACS admission so that the highest rate of admission was in summer. Consistent with this finding, Nastos et al 24 in Crete Island, Greece, reported the same pattern. In contrast, many other studies reported that the occurrence of myocardial infarction is associated with the winter season 28…”
Section: Discussionsupporting
confidence: 69%
“…Each year approximately 95% of the cold air affecting China passes through Gansu Province. Adverse weather conditions have a strong impact on the local residents’ lives and health, especially cardiovascular disease patients [24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…The relationships between human health and climate conditions have attracted people's attention for a long time. For example, Hippocrates expressed that patients and illness reasons should be considered inside the living environment in his Corpus Hippocraticum named book in 460-377 BC (Nastos et al, 2013). The investigations which produced the connections between climate conditions and human health have started to be studied mostly in the last 50 years.…”
Section: Introductionmentioning
confidence: 99%